THE POTENTIAL OF THE PEDOMAGNETIC INTERPRETATION AND MODELING FOR THE INCREASE OF THE EFFICIENCY OF THE MAGNETOMETRY INVESTIGATIONS - MENSHOV, O.; KHOMENKO, R.; SUKHORADA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The peculiarity of using the information about soil magnetism under detailed magnetometry investigations and pedomagnetic modeling is considered. The examples of the distributions of the investigated magnetic and magnetometric parameters in soils, the first results of the pedomagnetic modeling are described.